MAIN DUTIES AND FUNCTIONS OF THE HEAD OF ADMINISTRATION OF THE SOUTH SUWAWA HEALTH CENTER - Hadja, Dewi Pusvita; William Indra S. Mooduto; Siskawaty Yahya (Jurnal Ilmu Manajemen dan Bisnis, 2025)
This study aims to find out the Main Duties and Functions of the Head of Administration of the South Suwawa Health Center. The approach used in this study is a qualitative approach and a descriptive type of research. The type of research that can be used is qualitative, for the data sources that can be used are primary and secondary data. Of the 3 informants who have been interviewed, namely the Head of Administration of the Health Center, the Staff of the Health Center, and one of the people around the South Suwawa Health Center. We can find out that where the Main Tasks and Functions carried out by the Head of Administration of the South Suwawa Health Center have been running well, although there are still several obstacles such as lack of manpower, but this does not make the Suwawa Health Center managers give up to carry out services as much as possible.